Da'i Da'wah Method in Instilling Moral Values Anti-Promiscuity for Adolescents in Hutarimbaru Village - DEWI RAHMADANTI RAHMADANTI; Soiman (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
ABSTRACT Moral is an important position in Islam. A Muslim must be able to understand and apply good moral values in everyday life. Moral values are a form of realization of one's character. The rapid development of the times causes da'wah in adolescents as a challenge and requires systematic methods in instilling moral values. This study aims to examine and find out the da'wah method used by da'i in instilling anti-free promiscuity moral values in teenagers in Hutarimbaru SM Village, Mandailing Natal Regency. The type of research used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research subjects consisted of da'i, teenagers, and local community leaders. The results showed that there was a moral decline in teenagers in Hutarimbaru SM village, Mandailing Natal Regency. Some teenagers are affected by promiscuity that causes damage to moral values such as smoking at a young age, drugs, bullying, and early marriage, and there are even teenagers who are imprisoned. Furthermore, don't use da'wah methods of matzah, mujadalah, and personal approaches in conveying moral messages to instill moral values against promiscuity in teenagers in Hutarimbaru SM village. Keywords: Da'wah Method, Moral, Teenagers